Approach to assessment of prerequisites for innovative development of intellectual business - Sergii Illiashenko; Yuliia Shypulina; Nataliia Illiashenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article is devoted to developing an approach to identifying and assessing the sufficiency of prerequisites for the innovative development of intellectual business. The composition of internal and external prerequisites for innovative development of intellectual business in Ukraine is specified. Unlike existing approaches to internal prerequisites, the innovative culture of the intellectual business organization (innovator organization) is included, and the external ones include the innovative culture of its economic partners and contact audiences. This allows for assessing the level of innovation readiness of market entities (innovation process entities). Methodological principles for assessing the level of internal and external prerequisites are developed: assessment methodology, assessment scale. Decision tables are proposed for choosing the type of innovation development strategy depending on the ratio of the components of internal prerequisites (innovative capital and innovative culture of the innovator), as well as the ratio of innovative culture of the innovator and innovation consumers. A table of managerial decision-making has been developed regarding the feasibility of developing and implementing projects for innovative development of intellectual business according to selected types of strategies, depending on the correlations of its external and internal prerequisites. The principles for managing the choice of innovative development strategies and forming innovative development projects for intellectual business have been developed: a conceptual management scheme, a criteria base, the sequence and content of procedures for making managerial decisions. The obtained scientific results, conclusions, and recommendations in total deepen the principles of innovative management of enterprises and institutions in the conditions of the fourth industrial revolution and the transformation of technological ways. In particular, in terms of developing a methodological approach to assessing the sufficiency of external and internal prerequisites for managing the choice of innovative development strategies for enterprises and institutions of intellectual business, and the formation of relevant innovative projects.